Penerapan Zahir Accounting dalam Penyusunan Laporan Keuangan Toko Kue Rafita’s Cake - Surniandari, Artika; Putri, Anggita Novellia (LPPM Universitas Bina Sarana Informatika, 2023)
The development of information technology is the main reason for society to produce faster, more precise and accurate information. One form of this technology is software to process manual financial data into computerization. At Rafita's Cake Shop, accounting data processing is still done manually, therefore the authors suggest implementing a new system, namely a computerized system to avoid errors or risks that arise from processing accounting data manually. For this reason, the writer made a final assignment regarding processing financial accounting data using Zahir Accounting Version 6. The methods used in this research were observation, interviews and documentation related to this research. From this research it can be concluded that using Zahir Accounting processing financial data with a computerized system will be better than a manual recording system so that financial data processing becomes more effective, efficient and accurate.